Davao Agrarian Reform Beneficiaries Cooperative, Inc. - Tacay, Mary Joy P. (School of Management, University of the Philippines Mindanao, 2006)
The Davao Agrarian Reform Beneficiaries Cooperative (DARBCO), a disguised company, would like to rise from poor production performance and financial losses in 2004 and 2005. The board of directors would like to set the strategic direction by preparing a five year plan which is aligned with the Cooperative's vision, mission and values. The preparation of the strategic paper was based on a framework illustrated as a ribbon, which is commonly used by banana producers to monitor the different stages of fruit production. The study started with diagnostic procedures consisting of general situation review, evaluation of the external environment covering political, economic, sociological and technological aspects as well as evaluation of the internal environment covering human resources, operations and finance functions. After the diagnostic procedures, the strategic direction was determined in consultation with the board and validation of the strategic choice using the quantitative strategic planning matrix. The board reevaluated its mission, vision and values to align with its strategic choice. Finally, the implementation program was prepared consisting of: a. new mission, vision and goals; b. key result areas or the SMART (specific, measurable, attainable, realistic and time bound) objectives of the Cooperative; c. performance indicators to measure the attainment of the objectives; d. strategies, programs, activities and tasks to attain the objectives; and e. resources to be utilized in the plan. The Cooperative has identified major opportunities as government support, assistance from non-government organizations, government incentives, hedging of US dollar denominated transactions, trend towards growership, acceptance by the community, high investments in research by multinational banana producers and industry compliance with international standards. Major threats are unstable political system, high cost of compliance with environmental laws flat export markets, increasing production of Cavendish bananas, weak China imports and bad publicities on ill effects of chemicals. The Cooperative's ability to reach to its external environment is considered slightly unsatisfactory using external factor evaluation matrix as a tool. With respect to its internal environment, the Cooperative considered exercise of the right to elect officers, close proximity to the port, consolidated area, improved irrigation systems and technical and financial support from marketing partner as major strengths. These were however negated by lack of professional managers, high labor cost, division and demoralization, mono cropping for 100 years, susceptibility to blow downs, poor production performance and poor financial results as major weaknesses. The internal environment is deemed internally weak using the internal factor evaluation matrix as a tool. After the evaluation of the internal and external environments, the Cooperative identified three options for strategic direction. The board decided to go for Cost Leadership as a Cooperative. It is considered to be the most doable option in the near term. The choice was primarily based on contractual obligations and experience of the board. This is further validated using the quantitative strategic planning matrix. The board also considered 'individual farming' as an option where the land will be divided among members and each will decide whether to continue with Cavendish bananas or shift to other crops. Another alternative is "clustering of individual farms", where the area will be divided into smaller parcels of approximately 50 hectares each. Each cluster will run independently. The strategic plan for the next five years is focused on productivity, profitability and cost reduction. It also recognizes the need to have quality in processes and people as well as responsibility to other stakeholders. The board is optimistic to realize its plans and programs. The Cooperative is now in a better position to face the challenges.